2013
DOI: 10.1002/ar.22723
|View full text |Cite
|
Sign up to set email alerts
|

Is Mda‐7/IL‐24 a Potential Target and Biomarker for Enhancing Drug Sensitivity in Human Glioma U87 Cell Line?

Abstract: Gliomas are the most common form of primary brain tumor with the highest mortality rates. Drug resistance is a major cause of treatment failure in patients with glioma. Melanoma differentiation associated gene-7/interleukin-24 (mda-7/IL-24) has been demonstrated to play an important role in drug resistance in human cancer cell lines. However, the reversing effect of mda-7/IL-24 on drug resistance of human glioma is not fully clear. Here, we investigated the effects of overexpression of the mda-7/IL-24 gene in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several secreted factors, including tumor-associated inflammatory cytokines were shown to regulate autocrine/paracrine signaling in mediating the malignant transformation of tumor cells including chemoresistance [2628]. To explore the potential targets involving in MSI1-driven tumor-resistance in malignant glioma, we sought to in silico analyze the global gene expression profile to explore the impact of MSI1 overexpression in GBM cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several secreted factors, including tumor-associated inflammatory cytokines were shown to regulate autocrine/paracrine signaling in mediating the malignant transformation of tumor cells including chemoresistance [2628]. To explore the potential targets involving in MSI1-driven tumor-resistance in malignant glioma, we sought to in silico analyze the global gene expression profile to explore the impact of MSI1 overexpression in GBM cells.…”
Section: Resultsmentioning
confidence: 99%
“…Survivin is not always expressed in normal adult human tissues, but is expressed in many human cancers. It has been shown that survivin expression is closely associated with the degree of malignancy and prognosis of patients with cancers [ 38 , 39 ]. Our research showed that survivin expression levels were significantly decreased in mda-7/IL-24 over expressing cells, indicating that MDA-7/IL-24 is a negative regulator of survivin.…”
Section: Discussionmentioning
confidence: 99%
“…Our research showed that survivin expression levels were significantly decreased in mda-7/IL-24 over expressing cells, indicating that MDA-7/IL-24 is a negative regulator of survivin. Down regulation of Survivin increases the expression of caspases in cells, thus promoting apoptosis [ 38 ]. Activation of the family of caspases was known as a crucial mechanism for the induction of death signals to start apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interleukin-24 (IL-24) in glioma cells affects the sensitivity of gliomas to cisplatin by regulating the expression levels of P-gp and Bcl-2. IL-24 may be a biomarker predicting the sensitivity of gliomas to chemotherapy [ 69 ]. Peroxisome proliferator-activated receptor-γ (PPAR-γ) also plays an important role in regulating the sensitivity of glioma cells to cisplatin.…”
Section: Discussionmentioning
confidence: 99%